Konsepsi Disabilitas dan Pendidikan Inklusif - Yulianto, M. Joni (PLD UIN Sunan Kalijaga, 2014)
In the past decade, inclusive education has been a global rethoric and enjoyed significant scholarly attention. Drawing from Indonesian experience, this paper seeks to establish a clear link between disability and inclusive education. The author argues that the concept ofinclusive education in Indonesia is not yet well understood by the educational practioners and policy maker and consequently,has hampered the implementation of this policy in the field. It is only through appropriate understanding of disability that the concept of inclusive education would be better comprehended and implemented.Based on the examination of inclusive education policies and various aspect of its implementation, this paper also offers series of recommendation aimed for better impelementation of this policy in Indonesia. Among the recommendations are adequate resources, better political willingness, multi stake holder participation as well as wider support system.